Analisis Vicarious Liability dalam Pertanggungjawaban Rumah Sakit terhadap Gugatan Malpraktik Medis - Doddy Putra Pratama Sudjana; Deddy Effendi; Chepi Ali Firman Zakaria; Aslan Noor; Elsy Nur Anggraeni (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the application of the doctrine of vicarious liability in the liability of hospitals for medical malpractice lawsuits in Indonesia. The increasing number of medical disputes raises questions regarding the extent to which hospitals can be held responsible for the negligence of medical personnel working under their authority. This research employs a normative juridical method with statutory, conceptual, and case approaches, by examining the Indonesian Civil Code, Law No. 44 of 2009 on Hospitals, Law No. 17 of 2023 on Health, and relevant court decisions. The findings reveal that, normatively, hospitals can be held accountable under Article 1367 of the Civil Code, which aligns with the doctrine of vicarious liability (Black, 2019). However, judicial practice in Indonesia remains inconsistent: in some cases judges place liability on hospitals, while in others they hold individual doctors fully responsible (Budiman, Absori & Rizka, 2023; Vitrianingsih, Miarsa & Yahya, 2025). This inconsistency demonstrates a gap between normative regulation and juridical implementation. The novelty of this study lies in emphasizing the importance of the principle of justice in applying vicarious liability. Legal protection should not be limited to written norms but must also be substantive by balancing patients’ rights to safe and quality healthcare with the rights of medical personnel and hospitals to legal certainty. This is in line with Rawls’ (1971) concept of justice as fairness and Radbruch’s (2006) idea of balancing justice, legal certainty, and expediency.